Proniosomal gel-derived niosomes: an approach to sustain and improve the ocular delivery of brimonidine tartrate; formulation, in-vitro characterization, and in-vivo pharmacodynamic study - Alaa Emad Eldeeb; Salwa Salah; Mahmoud Ghorab (Taylor & Francis Group, 2019)
Brimonidine tartrate (BRT) is a hydrophilic α2 adrenergic agonist used for the treatment of glaucoma. Glaucoma is an ocular disease affecting the anterior segment of the eye requiring lifetime treatment. Owing to the obstacles facing ocular delivery systems and hydrophilicity of BRT, frequent administration of the eye drops is required. Niosomes have been widely used to improve the ocular bioavailability of the topically applied drugs and to enhance the ocular residence time. However, they have drawbacks as physical instability, aggregation, and loss of the entrapped drug. For this reason, BRT proniosomes were prepared to overcome niosomal instability issues. A D-optimal design was utilized to determine the optimum conditions for preparation of the proniosomal gels. Independent variables were amount of surfactant, surfactant:cholesterol ratio, and type of surfactant used. The dependent variables were entrapment efficiency (EE%), particle size, percentage of drug released after 2 h (Q2h), and percentage of drug released after 24 h (Q24h). The optimum formula was suggested with desirability 0.732 and the composition of 540 mg Span 60 and 10:1 surfactant:cholesterol ratio. The results obtained after reconstitution were; EE% of 79.23 ± 1.12% particle size of 810.95 ± 16.758 nm, polydispersity index (PDI) 0.6785 ± 0.213, zeta potential 59.1 ± 0.99 mV, Q2h40.98 ± 1.29%, Q8h 63.35 ± 6.07%, and Q24h = 91.11 ± 1.76%. Transmission electron microscope imaging of the formula showed the typical spherical shape of niosomes. In-vivo pharmacodynamic study assured the improved ocular bioavailability of BRT selected formula when compared with Alphagan®P with relative AUC0-24 of 5.024 and 7.90 folds increase in the mean residence time (MRT). Lack of ocular irritation of the formula was assured by Draize test.